Optimal Scheduling of the Leaves of a Tree and the SVO Frequencies of Languages - Papadimitriou, Christos H.; Turcu, Denis (Learning and Intelligent Optimization, 2023)
We define and study algorithmically a novel optimization problem related to the sequential scheduling of the leaves of a binary tree in a given order, and its generalization in which the optimum order is sought. We assume that the scheduling process starts at the root of the tree and continues breadth-first in parallel, albeit with possible intervening lock and unlock steps, which define the scheduling cost. The motivation for this problem comes from modeling language generation in the brain. We show that optimality considerations in this problem provide a new explanation for an intriguing phenomenon in linguistics, namely that certain ways of ordering the subject, verb, and object in a sentence are far more common in world languages than others.